Measuring mode indices of a partially coherent vortex beam with Hanbury Brown and Twiss type experiment - Liu, Ruifeng; Wang, Feiran; Chen, Dongxu; Wang, Yunlong; Zhou, Yu; Gao, Hong; Zhang, Pei; Li, Fuli (Applied physics letters, 2016)
It is known that the cross-correlation function (CCF) of a partially coherent vortex (PCV) beam shows a robust link with the radial and azimuthal mode indices. However, the previous proposals are difficult to measure the CCF in practical systems, especially in the case of astronomical objects. In this letter, we demonstrate experimentally that the Hanbury Brown and Twiss effect can be used to measure the mode indices of the original vortex beam and investigate the relationship between the spatial coherent width and the characterization of CCF of the PCV beam. The technique we exploit is quite efficient and robust, and it may be useful in the field of free space communication and astronomy which are related to the photon's orbital angular momentum.